HISTORICAL CLASSIFICATION AND TERMINOLOGY OF ARCHITECTURE IN THE INDIAN SUBCONTINENT - Ali syed (Frontline Social Sciences and History Journal, 2024)
The architectural heritage of the Indian subcontinent is a rich tapestry woven from diverse influences, styles, and traditions that span several millennia. Understanding this heritage requires a nuanced grasp of the historical classification and terminology that define various architectural periods and styles. This abstract provides an overview of the classification systems and terminological frameworks used in the study of the architecture of the Indian subcontinent, highlighting their significance and evolution. Historical Classification: Architecture in the Indian subcontinent can be classified into several major periods based on historical, cultural, and stylistic criteria. The primary periods include: Ancient Period (up to 6th century CE): This period encompasses early architectural forms such as the rock-cut caves, Buddhist stupas, and Hindu temples. Notable examples include the Ajanta and Ellora caves and the Sanchi Stupa. This period is characterized by its focus on religious and ritualistic structures, with a strong emphasis on symbolic representation. Medieval Period (7th to 16th centuries CE): The medieval period is marked by the rise of distinct regional styles and the construction of grand temples and forts. The Dravidian style, prevalent in South India, features intricately carved temple towers (Shikharas) and large courtyards. In contrast, the Nagara style, dominant in North India, is known for its curvilinear towers and complex temple layouts. The Islamic influence introduced by various dynasties, such as the Delhi Sultanate and Mughal Empire, brought new elements, including domes, minarets, and expansive gardens. Colonial Period (17th to mid-20th centuries CE): The arrival of European powers, particularly the British, introduced colonial architectural styles that fused Western elements with traditional Indian forms. This period saw the construction of monumental buildings such as the Victoria Terminus (now Chhatrapati Shivaji Maharaj Terminus) and the Rashtrapati Bhavan, reflecting a blend of Gothic, Neoclassical, and Indo-Saracenic styles. Post-Independence Period (mid-20th century onwards): After India gained independence in 1947, there was a shift towards modernist architecture. This period is characterized by experimentation with new materials, techniques, and international styles. Prominent architects like Charles Correa and B.V. Doshi contributed to the development of modern Indian architecture while incorporating local traditions and climate-responsive designs.